Correlation and path coefficient analyses of yield and yield components of eggplant (Solanum melongena) in a coarse-textured Ultisol - Vincent N. Onyia; Uchechukwu Paschal Chukwudi; Augustus Chika Ezea; Agatha I. Atugwu; Chikezie O. Ene (Information Processing in Agriculture, 2020)
Assessment of variability and understanding of traits relationship in eggplant species are vital pre-requisite for formulating an effective breeding programme. We studied 23 genotypes of eggplants in a coarse-textured Ultisol using a randomized complete block design experiment with three replications. Data were collected on number of branches, number of leaves, number of nodes and internodes, stem diameter, plant height, floral and yield traits. Results revealed significant (p = 0.05) variation in the flowering and fruiting pattern of the genotypes. ‘Yalo x K3BC2P1′ gave the highest individual fruit weight of 80.8 g. Individual fruit weight contributed the highest direct positive effect on the fruit yield. It acted majorly through plant height, number of branches, number of leaves and number of days to first fruit set as revealed in the path coefficient result. Individual fruit weight, number of fruits per plant, plant height, number of days to 50% flowering, number of branches, numbers of days to first flowering and 50% fruit set had positive direct effect on yield. These traits should be considered in developing high yielding eggplant breeding programme. Keywords: Correlation, Genetic improvement, Path coefficient, Solanum melongena, Ultisol, Yield